Maternal Immunity Influences Vertical Transmission of Hepatitis B to Newborns - Vyas, Ashish Kumar (Hepatol Commun, 2019)
Vertical transmission of hepatitis B virus (HBV) from the mother to the newborn often results in viral persistence. To understand mechanisms of maternofetal HBV transmission, we studied maternal immunity and peripheral blood mononuclear cell (PBMC) transcriptome in mothers and newborns. We included 50 mothers and babies who were hepatitis B surface antigen (HBsAg) positive: 22 HBV transmitting mothers (group [Gr.] I) and 28 HBV nontransmitting mothers (Gr. II) to newborns and 10 healthy mother–baby pairs (Gr. III). PBMCs were analyzed for HBV‐specific dendritic cells (DCs), T cells, T follicular helper (TFh) cells, B cells, functional immune responses, and cytokine levels as well as transcriptome signatures to identify immune gene expression correlates for protective immunity. Group II mothers had lower HBsAg levels (3.82 × 10(3) versus 1.493 × 10(4); P < 0.0001) with greater HBV‐specific responses of DCs, T cells, TFh cells, and B cells than Gr. I mothers. Frequencies of TFh cells were lower in Gr. I mothers, with reduced interleukin‐21 (IL‐21) levels, and these inversely correlated with HBV DNA levels. Cut‐off levels of 9.5% and 8.93% from the receiver operating curve predicted the involvement of TFh cells and B cells in HBV transmission. Transcriptome signatures revealed that maternal gene imprints were reflected in the newborns. Genes related to DCs, TFh cells, and B cells were increased in Gr. II, and Gr. II newborns showed a boost in cellular and humoral responses after vaccination. Conclusion: In mothers infected with HBV, low serum IL‐21 levels and decreased TFh‐cell and plasma B‐cell frequencies are associated with vertical transmission of HBV to newborns. These features are indicative of low protective maternal immunity.